Câncer da mama-estudo retrospectivo e comparativo do perfil epidemiológico das pacientes em três diferentes faixas etárias - Perea, Silvia Aparecida (1998)
A retrospective study in patients carriers of breast cancer was performed during the period of January, 1993 to December, 1997. Two hundred nineteen cases were diagnosed and divided in three groups according to the age group: under age 40 (35 cases or 16%), 41 to 60 years old (116 cases or 53%) and the age of 61 or more (68 cases or 31%). The aim of this study was to check breast cancer prevalence among young women (under age 40) and analyze epidemiologic data among the groups, comparing with the literature. The following parameters showed significant results: marital status, origin, profession, age of menarche, number of gestation and pregnancies, contraceptive method and findings of phisical exams. Race, menstrual cycle, number of abortion, age of the first livebirth, cigarette smoking, fat intake, corporal weight, family and personal history, clinical stadium and histopathological exams showed no significant results. Based on those results, it was concluded that young patients compared to older ones, did not present significant differences in the data analysis and also according to the literature they were not adjusted in that epidemiologic profile classically described.